Ocular and neurological Behçet's disease without orogenital ulceration?. Issue 5 (May 1993) - Lueck, C J; Pires, M; McCartney, A C; Graham, E M
Abstract : A 28 year old West Indian patient is described who had a relapsing and remitting steroid-sensitive illness for 3 years. The clinical features included uveitis and widespread CNS involvement. The patient was treated as though he had neurosarcoidosis. Post mortem examination revealed histological changes compatible with a diagnosis of Behçet's disease, but at no time did he suffer from oral or genital ulceration or arthritis. The authors suggest a new term to encompass such an entity: the "Behçet's MINUS" syndrome (multifocal intermittent neurological and uveitic syndrome).